Quality Organizational Culture, Job Satisfaction, Job Resources & Rewards On Employees ' Work Engagement At Hospital In Makassar - Anshar, Achmad; Pasinringi, Syahrir A.; Arifah, Nur; Rivai, Fridawaty; Sidin, Andi Indahwaty; Sangkala, Sangkala; Mallongi, Anwar (Journal of Neonatal Surgery, 2025)
At Hospital X in Makassar City, employee turnover data in 2021 was 19.58%. While in 2022, turnover data at the hospital was 20.18% and in 2023 it was 20.90%. The purpose of this study was to determine the quality of organizational culture, job satisfaction, job resources & rewards on employee work engagement at Hospital X Makassar. The determination of informants used the purposive sampling method and obtained 17 informants . Data validation tests were carried out using source triangulation and technique triangulation . The results of the study showed that employees at hospital X showed freedom in decision-making that was carried out in accordance with the SOP and the responsibilities of their work units, which reflected the existence of good responsibility and work ethic from employees . However , there is a need for increased transparency of information related to promotions and the provision of special competency training. Meanwhile, the family atmosphere in the hospital work environment plays an important role in increasing job satisfaction and employee enthusiasm in providing beneficial services to patients. Various backgrounds and expertise among employees, mutually supportive relationships and a sense of togetherness can create a positive and inclusive work environment. In this case, job satisfaction is a variable that plays an important role in increasing work engagement in hospital X. This researcher suggests that the hospital create inclusive policies that support diversity in the workplace and ensure that all employees feel valued and accepted, implement reward programs to recognize outstanding performance and contributions from employees, provide ongoing career development and training programs for employees, and conduct regular employee engagement surveys to measure their level of job satisfaction and engagement